Emergence of rating agencies: Implications for establishing a regional rating agency in Asia - Ying Yi Tsai; Li-gang Liu (Asian Development Bank Institute (ADBI), 2010)
The present analysis sheds light on the setting up a regional rating agency in Asia in the wake of recent financial crisis. We investigate the policy facing a financial regulator while evaluating whether or not to admit new entrants into the credit rating market. In an incomplete contracting framework, we show that an impartial financial regulatory body (represented by a benevolent supranational organization) can facilitate credit ratings of high quality by allowing for the entry of new rating agencies on a non-single basis than it does for a mere single entry. This finding is caused by increased competition among the rating agencies, which induces higher quality of rating services even should rating agencies still exert below their maximum level of efforts.
Keywords: D43; D82; G24; L15; 330; Ratingagentur; Internationale Organisation; Kapitalmarktliberalisierung; Regulierung; Entscheidung bei Risiko; Unvollkommener Markt; Theorie